Nilai Budaya dan Makna Simbolis Seni Tradisional Jepang Daruma, Okinasan, Koi-nobori, dan Nagashi-bina - Reny Wiyatasari (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2019)
This article aims to explain the cultural value and symbolic meaning contained in traditional Japan’s folk arts (mingei). Of the many traditional folk arts in Japan, only four of them are used as the topic of discussion of this article, namely Daruma, Okinasan Koi-nobori, and Nagashi-bina. All four are interesting to study because they contain cultural values and symbolic meanings that illustrate the cultural concepts of Japanese society, both in character and beliefs that are still held and maintained today. Data collection was carried out through literature and interview methods, and analyzed using qualitative analysis techniques.